1997
DOI: 10.1046/j.1471-4159.1997.69041398.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophic Effects of l‐DOPA in Postnatal Midbrain Dopamine Neuron/Cortical Astrocyte Cocultures

Abstract: L-DOPA IS toxic to catecholamine neurons in culture, but the toxicity is reduced by exposure to astrocytes. We tested the effect of L-DOPA on dopamine neurons using postnatal ventral midbrain neuron/cortical astrocyte cocultures in serum-free, glia-conditioned medium. L-DOPA (50 tiM) protected against dopamine neuronal cell death and increased the number and branching of dopamine processes. In contrast to embryonically derived glia-free cultures, where L-DOPA is toxic, postnatal midbrain cultures did not show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(71 citation statements)
references
References 69 publications
6
65
0
Order By: Relevance
“…The effect of catecholamines on survival has been studied so far only in mammalian cells (Han et al, 1996;Mena et al, 1997;Varella et al, 1999) However, it has been shown that apomorphine, a dopamine agonist, and its oxidation product 8-oxo-seimiquinone are toxic for the cells, but sublethal concentrations enhance survival when cells are pretreated with other oxidants (Picada et al, 2003). It also has been suggested that l-dopa as well as dopamine stimulate the MAPK activity of the classical extracellular signal-regulated kinase (ERK) pathway in neuronally derived cultured PC12 cells (Yan et al, 1999;Koshimura et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of catecholamines on survival has been studied so far only in mammalian cells (Han et al, 1996;Mena et al, 1997;Varella et al, 1999) However, it has been shown that apomorphine, a dopamine agonist, and its oxidation product 8-oxo-seimiquinone are toxic for the cells, but sublethal concentrations enhance survival when cells are pretreated with other oxidants (Picada et al, 2003). It also has been suggested that l-dopa as well as dopamine stimulate the MAPK activity of the classical extracellular signal-regulated kinase (ERK) pathway in neuronally derived cultured PC12 cells (Yan et al, 1999;Koshimura et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The catecholamines have been shown to be toxic because of their ability to oxidize and produce reactive oxygen species and quinones in contrast to the other tested structural analogues of l-dopa that do not undergo autooxidation (Basma et al, 1995;Han et al, 1996;Mena et al, 1997). We hypothesized that l-dopa and the other catecholamines activated the yeast mating MAPK via autooxidation by forming reactive oxygen species.…”
Section: The Stimulatory Effect Of L-dopa On Fus1 and Rlm1 Transcriptmentioning
confidence: 99%
“…Many in vitro studies showed toxic effects of L-DOPA on midbrain dopaminergic neurons but its toxicity has not been proven in vivo (reviewed by Olanow et al, 2004). In fact, trophic effects of L-DOPA were observed on dopaminergic neurons cocultured with astrocytes (Mena et al, 1997) but, to our knowledge, our group is the only describing the effect of L-DOPA on GDNF levels in the nigrostriatal system. We have shown that L-DOPA induces GDNF up-regulation at the mRNA and protein levels in substantia nigra neuron-glia cell cultures, in a process involving soluble mediators that signal astrocytes to increase GDNF expression (Saavedra et al, 2006).…”
Section: L-dopamentioning
confidence: 94%
“…Postnatally derived cultures of midbrain neurons were prepared as described earlier (Rayport et al, 1992) except that serumfree medium was used (Mena et al, 1997). Recordings were performed 3-6 weeks postplating.…”
Section: Primar Y Culturesmentioning
confidence: 99%